Late Holocene Orbital Forcing and Solar Activity on the Kuroshio Current of Subtropical North Pacific at Different Timescales - Ding, Xue; Hu, Bangqi; Li, Jun; Zhao, Jingtao; Yao, Yue; Li, Qing; Lan, Jianghu; Zheng, Xufeng; Yi, Liang (Frontiers in Earth Science, 2022)
North Pacific subtropical gyre (NPSTG) redistributes heat and moisture between low and high latitudes and plays a key role in modulating the global climate change and ecosystem. Recent evidence suggests intensification and poleward shift of the subtropical gyres over the last decades due to the global warming, but insufficient observations have hampered insight into the integrated effects of ocean-atmosphere interactions at longer timescales. Here we present the first high-resolution (~12 years) grain-size record from Core CF1 in the Okinawa Trough, western subtropical North Pacific, to reconstruct the evolution of western boundary current (Kuroshio Current, KC) of NPSTG during the Late Holocene. Our results indicate the KC slow-down during 4.6–2.0 ka, followed by quickly enhanced after 2.0 ka, with centennial‐scale variabilities (500-700 years) superimposed on the long-term trend. Over millennial timescales, gradually increased pole-to-equator thermal gradient due to orbital forcing mechanisms resulted in long-term enhanced KC, whereas solar activity triggered phase changes in the tropical Pacific mean state and controlled KC anomalies on centennial timescales. We suggest that both forcing mechanisms resulted in ocean-atmosphere feedback provoking concurrent changes in mid-latitude westerly and subtropical easterly winds over the North Pacific, alternating their dominance as source regions cause the dynamic changes of KC at different timescales. Our findings offer insights into the role of external forcing mechanisms in the NPSTG changes before the Anthropocene, which have profound implications for the deeper understanding of changes in ocean gyres under global warming scenarios.